2002
DOI: 10.1039/b207024n
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded polymer network—poly(ethylene glycol) complexes with shape memory effect

Abstract: Complexes of a poly(methacrylic acid-co-methyl methacrylate) network with poly(ethylene glycol) stabilized by hydrogen bonds were prepared. By introducing poly(ethylene glycol), the complexes possessed shape memory effect, due to which a large difference in storage modulus below and above the glass transition temperature occurred. The morphology of the complexes was investigated and the mechanism of the shape memory behavior was discussed. This kind of complexes can be regarded as a novel shape memory network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 20 publications
(20 reference statements)
0
47
0
Order By: Relevance
“…Most current shape memory polymers known are block copolymers or crosslinked polymer networks, which are introduced two phases structure by covalently linking method 5, 6. Only more recently, Peng and coworkers7–9 have developed some supramolecular shape‐memory materials, which were self‐assembled by electrostatic interaction or hydrogen bond between two polymers. But the relative researches are few and the polymer complexes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Most current shape memory polymers known are block copolymers or crosslinked polymer networks, which are introduced two phases structure by covalently linking method 5, 6. Only more recently, Peng and coworkers7–9 have developed some supramolecular shape‐memory materials, which were self‐assembled by electrostatic interaction or hydrogen bond between two polymers. But the relative researches are few and the polymer complexes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we can see that a difference of two orders of magnitude of the high elasticity ratio between glassy state modulus (E g ) and rubbery modulus (E r ) was obtained in the SMPs. Therefore, the NGDE/PBA-a SMPs are easy shaping at T > T s (shape memory temperature) and they show great resistance to deformation at T < T s [41]. Loss tangent (tan ") curves from a DMA experiment of the NGDE/PBA-a SMPs at various BA-a contents are depicted in Figure 6.…”
Section: Dynamic Mechanical Analysis Of Ngde/pba-a Smpsmentioning
confidence: 99%
“…Here, the storage modulus ratio (E 0 ratio being defined as E 0 T g À20 C =E 0 T g þ20 C ) can be more than 400 for one of the designed polymers in Figure 4, while that of P(AA-co-MMA)/PEG complexes at best reaches 170. [12,13] A shape-memory polymer basically contains a fixing phase and a reversible phase. The fixing phase imparts a level of rigidity, dimensional stability, and thermal resistance, while the reversible phase provides the elastic properties, primarily recovery and energy absorption.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Up to now, most of the reports on shape-memory polymers introduced the switching segments by using the covalent linking method, [3][4][5][6][7][8][9][10] while few cases concern the non-covalent interaction. [2,11,12] In a previous study, we reported that the complex of polyelectrolyte network with surfactant and the hydrogen-bonded polymer network-poly(ethylene glycol) (PEG) complex shows shape-memory effect. [11][12][13] Following our previous Summary: Due to a large difference in storage modulus below and above the glass transition temperature, a novel shapememory poly[(methyl methacrylate)-co-(N-vinyl-2-pyrrolidone)]/poly(ethylene glycol) semi-interpenetrating polymer networks structure was synthesized, which is stabilized by hydrogen-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%